IDENTIFIKASI CACAT AKUSTIK PADA INTERIOR GEDUNG NASIONAL KALIMANTAN TIMUR DI KOTA SAMARINDA (Identification Of a Acoustic Defects In The Interior Of East Borneo National Building In Samarinda City) - Maulana Refindo Dhuhur; Antonius Ardiyanto; B. Tyas Susanti (Universitas Katolik Soegijapranata, 2026)
The East Borneo National Building is a conservation building established over 50 years ago, serving as a multi-purpose auditorium for various art and community events in Samarinda city. Over the last year, a 40% decline in usage has been observed, driven by user complaints regarding poor room acoustics. This issue forms the background and urgent objective of the current research to revitalize the use of the building. Initial field observations suggest the problem lies with room acoustics, speciafically the uneven sound distribution, which affects listener comfort. A subsequent questionnaire survey of 33 building users revealed that approximately 60% reported non-uniform sound dissemination within the auditorium. This finding was supported by sound level meter measurements which indicated an imbalance in sound intensity across different points in the room. The research employed a quantitative methodology, involving field observation, sound pressure level measurement using an sound level meter and sound distribution simulation utilizing the I-SIMPA acoustic software. The findings reveal that measurement points in the rear auditorium area and the area under the mezzanine floor exhibit relatively lower sound pressure level values compared to other areas, identifying an acoustic defect known as a sound shadow.